Equilibrium and Welfare Analysis in Second-Price Auctions with Resale and Costly Entry - Xiaoyong Cao; Yunxia Yang; Yuntao Yang; Siru Li (Discrete Dynamics in Nature and Society)
This study investigates the effects of resale allowance on entry strategies, seller’s expected revenue, and social welfare in a second-price auction with two-dimensional private information on values and participation costs. We characterize the perfect Bayesian equilibrium in cutoff strategies and identify sufficient conditions under which the equilibrium is unique. Our analysis suggests that resale allowance leads the low-value bidder to become more aggressive on entry, while high-value bidder has a lower incentive to enter. Furthermore, the allowance of resale can increase the social welfare under a sufficient condition, and its effect on expected revenue is ambiguous.